A Model for Enhancing the Competency of Buddhist Integrative Teacherhood in of Students in Faculty of Education, Rajabhat University - Udomphol, Boonruedee (The Journal of Development Administration Research, 2020)
The purposes of this study were to: 1) study the teacher competency status of the students in the faculty of education, Rajabhat university 2) present a model for enhancing competency of being an integrated Buddhist teacher of the students in the faculty of education, Rajabhat university, This study employed mixed methods of research based on the qualitative research by studying documents, in-depth interview with 5 administrator and instructors. Focus group discussion of 12 experts. The instruments used in this research were documentary study form, in-depth interview. The quantitative research. A group of samples was selected from administrators and teachers in the faculty of education, Rajabhat university, 400 persons. In which the researcher selected the criteria for determining the sample size of comrey & Lee, proposed that the sample size that is suitable for use in composition analysis is 300 persons, it is considered good. And use the rules of practice (Rule of Thumb) At the faculty and staff. The researcher specifies the sample size of 5 times the sample. Therefore, the researchers set the sample size of 440 people to make the research results more consistent with the fact data. By using the multistage random sampling method (Multi-Stage Random Sampling). The research instruments were questionnaires, evaluation of teacher competence, document analysis, content analysis, and statistical analysis. The research results found that; 1. Teacher Competency Status of Students in the Faculty of Education Rajabhat University is as follows 1) Students lack the link between content and learning management methods. 2) Students lack the spirit of being a teacher and professional teaching ethics. 3) Students lack in volunteering, Relations with parents, Communities, and networking.4) Students are unable to organize learning that promotes thinking and 21st-century skills.1.5 The competency of the teacher that students should be strengthened to meet the standards of teachers there are 5 components, 88 items such as.5 1) The teacher must be knowledgeable. There are 17 points. 2)Teachers need to proactively manage learning to develop students. There are 14 points. 3) The teachers who acted as good. There are 18 points. 4) Professional and professional development. There are 17 points. 5)The teacher creates relationships with parents and communities. There are 19 points. 2. The result of examination and evaluation of the model of enhancing the competency of being an integrated Buddhist teacher of students in the Faculty of Education, Rajabhat University was consists of 5 parts which are 1) Principles 2) Objectives 3) The process of teacher competency development 4) Application, and 5) Achievement condition and it was at a high level totally. In details, the highest level was on usefulness, followed by accuracy, appropriateness, and feasibility respectively.